Boosting EFL Public Speaking: How Preparedness and Self-Confidence Impact Willingness to Communicate - Cenderato, Cenderato (JET ADI BUANA, 2026)
This study investigates the impact of preparedness, self-confidence, and willingness to communicate (WTC) on public speaking among 52 first-semester EFL students at STAKatN Pontianak. Utilizing a correlational design, the results indicate that both preparedness and self-confidence significantly drove WTC. Specifically, preparedness—encompassing communicative competence and affective readiness—enables oral production through situational preparedness, while self-confidence reduces anxiety and enhances perceived ability across classroom and digital settings. Together, these factors create a reciprocal cycle: they diminish avoidance behaviors and foster positive emotional states like grit, leading to long-term fluency gains. Practically, these findings suggest that educators should prioritize "psychological scaffolding"—such as pre-task planning and anxiety-reduction activities—to boost students' vocal participation. However, the study is limited by its small, localized sample size and its reliance on self-reported data, which may not fully capture spontaneous speaking behavior outside the classroom. Future research should incorporate longitudinal observations to determine if these psychological traits consistently translate into sustained proficiency in professional, non-academic environments.